Coagulation mechanism of polyaluminum manganese chloride in alkaline conditions: Role of manganese in changing hydrolysates and coordination structure - Yanli Kong; Pengjun Zhang; Shunliang Hu; Yunlong Xie; Zhonglin Chen; Jiangya Ma (Journal of Environmental Sciences, 2026)

Immune-oligonucleotide nanocomplex for ions release control (IONIC) mediated simultaneous rapid one-step homogeneous electrochemical immunoassay of multiple targets - Pengjun Jiang; Yue Wang; Ying Xiong; Jie Chen; Yi Xie; Binwu Ying; Piaopiao Chen (Chemical Engineering Journal, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Quantifying ship-bridge collision risk through extreme value theory: a new methodological framework - Xi Chen; Hongzhu Zhou; Meng Li; Manel Grifoll; Yusheng Zhou; Jiao Liu; Pengjun Zheng (Ocean Engineering, 2026)

Constructing of an NH2-MIL-53(Fe)/g-C3N4 adsorptive photo-Fenton system for efficient degradation of norfloxacin in medical wastewater - Ziqi Deng; Yating Chen; Pengjun Duan; Rong Cheng; Jianzhong Zheng; Xiang Zheng (Chemical Engineering Journal, 2026)

Triple parallel rolling circle amplification aid DNA hydrogel/QDs-based programmable aptasensor for targets profiling - Ying Xiong; Yue Wang; Xin Jiang; Xianghu Zeng; Pengjun Jiang; Bofu Liu; Binwu Ying; Yi Xie; Piaopiao Chen (Chemical Engineering Journal, 2025)

GeoAvatar: A big mobile phone positioning data-driven method for individualized pseudo personal mobility data generation - Peiran Li; Haoran Zhang; Wenjing Li; Dou Huang; Zhiling Guo; Jinyu Chen; Junxiang Zhang; Xuan Song; Pengjun Zhao; Jinyue Yan; Shibasaki Ryosuke; Noboru Koshizuka (Computers, Environment and Urban Systems, 2025)

New perspectives on urban stormwater management in China, with a focus on extreme rainfall events - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiuling Chen; Qiang Wang; Jun Xia (Natural Hazards, 2025)

Assessing vessel transportation delays affected by tropical cyclones using AIS data and a bayesian network: A case study of veronica in northwestern Australia - Caixia Zhang; Pengjun Zhao; Zhucheng Huang; Zhangyuan He; Yingnan Niu; Guangyu Huang; Yuting Chen (Ocean Engineering, 2024)

Biomolecule-regulation of fluorescent probe signaling: Homogeneous rapid portable protease sensing in serum - Yalan Zhu; Pan Feng; Pengjun Jiang; Kai Li; Ke Huang; Jie Chen; Piaopiao Chen (Analytica Chimica Acta, 2024)

Exploring interactive and nonlinear effects of key factors on intercity travel mode choice using XGBoost - Xiaowei Li; Lanxin Shi; Yang Shi; Junqing Tang; Pengjun Zhao; Yuting Wang; Jun Chen (Applied Geography, 2024)

Safety or efficiency? Estimating crossing motivations of intoxicated pedestrians by leveraging the inverse reinforcement learning - Yun Ye; Pengjun Zheng; Haoyang Liang; Xiqun Chen; S.C. Wong; Pengpeng Xu (Travel Behaviour and Society, 2024)

Biotechnological production of ectoine: current status and prospects - Jun Chen; Deliang Qiao; Tao Yuan; Yeyuan Feng; Pengjun Zhang; Xuejun Wang; Li Zhang (Folia Microbiologica, 2024)

Characterization and genomic analysis of a novel bacteriophage BUCT_49532 lysing Klebsiella pneumoniae - Guangye Zhang; Yucong Liu; Jinhong Wang; Nan Li; Pengjun Han; Yiming Chen; Weijian Xu; Changxia Liu (Virus Genes, 2023)

Effect of different multichannel ventilation methods on aerobic composting and vegetable waste gas emissions - Ruirong Li; Liang Cai; Jie Cao; Pengjun Wang; Haoli Qu; Mingjiang Chen; Yongsheng Chen (Environmental Science and Pollution Research, 2023)

Enhancing catalytic performance of Fe and Mo co-doped dual single-atom catalysts with dual-enzyme activities for sensitive detection of hydrogen peroxide and uric acid - Jin Chen; Jiali Zhong; Juanhua Lai; Zoujun Peng; Tao Lian; Xiaomin Tang; Pengjun Li; Ping Qiu (Analytica Chimica Acta, 2023)

Anti-sine-cosine atom search optimization (ASCASO): a novel approach for parameter estimation of PV models - Wei Zhou; Pengjun Wang; Xuehua Zhao; Huiling Chen (Environmental Science and Pollution Research, 2023)

Experimental Study of Hot Spot Stress for Spatial CHS KK-Joints - Kang Wang; Yuhang Wang; Shan Gao; Bin Wang; Jinzhong Chen; Pengjun Luo (Journal of Marine Science and Engineering, 2023)
In offshore structures such as offshore wind turbine jacket foundations, prolonged exposure to wind and wave loads can lead to fatigue failure, especially at the joint connections. Currently, international codes primarily evaluate the fatigue performance of tubular joints using the hot spot stress (HSS) method, with stress concentration factor (SCF) being the most crucial parameter. Numerous studies have investigated the SCF of tubular joints and proposed corresponding calculation formulas. However, most of these studies have focused on simple basic loading cases. To comprehensively understand the distribution pattern of the HSS method at spatial tubular joints, this study selects the spatial CHS KK-joints as the research subject and performs the HSS testing on spatial KK-joints. The research indicates that, in CHS joints, the distribution of the HSS on the chord side remains consistent under tensile or compressive loading conditions along the brace axis. Additionally, within spatial joints, the loading conditions of neighboring braces near the reference brace significantly affect the distribution of HSS on the chord side and exhibit varying spatial effects on the SCF. Furthermore, this study applies recommended calculation formulas from codes to analyze the experimental results. The findings reveal significant discrepancies between the SCF calculation formulas recommended by CIDECT and the test results, rendering it inadequate for accurately calculating the SCF of spatial KK-joints. Therefore, further research is required to develop suitable calculation formulas for SCFs in spatial KK-joints.

Tree diversity increases soil C and N stocks of secondary forests in subtropical China - Zaixiang Yuan; Qingwei Guan; Xinli Chen; Pengjun Zou; Yuqing Gu; Qian Wu; Yingying Niu; Appiah Ofori Meshack (CATENA, 2023)

Anomalous Ru dissolution enabling efficient integrated CO2 electroreduction in strong acid - Beibei Sheng; Dengfeng Cao; Hongwei Shou; Wenjie Xu; Chuanqiang Wu; Pengjun Zhang; Chongjing Liu; Yujian Xia; Xiaojun Wu; Shengqi Chu; Jing Zhang; Li Song; et al. (Chemical Engineering Journal, 2023)

Revisiting the gravity laws of inter-city mobility in megacity regions - Pengjun Zhao; Haoyu Hu; Liangen Zeng; Jun Chen; Xinyue Ye (Science China Earth Sciences, 2023)
Inter-city mobility is one of the most important issues in the UN Sustainable Development Goals, as it is essential to access the regional labour market, goods and services, and to constrain the spread of infectious diseases. Although the gravity model has been proved to be an effective model to describe mobility among settlements, knowledge is still insufficient in regions where dozens of megacities interact closely and over 100 million people reside. In addition, the existing knowledge is limited to overall population mobility, while the difference in inter-city travel with different purposes is unexplored on such a large geographic scale. We revisited the gravity laws of inter-city mobility using the 2.12 billion trip chains recorded by 40.48 million mobile phone users’ trajectories in the Jing-Jin-Ji Region, which contains China’s capital Beijing. Firstly, unlike previous studies, we found that non-commuting rather than commuting is the dominant type of inter-city mobility (89.3%). Non-commuting travellers have a travel distance 42.3% longer than commuting travellers. Secondly, we developed more accurate gravity models for the spatial distribution of inter-city commuting and non-commuting travel. We also found that inter-city mobility has a hierarchical structure, as the distribution of inter-city travel volume follows Zipf’s law. In particular, the hierarchy of non-commuting travel volume among the cities is more in line with an ideal Zipf distribution than commuting travel. Our findings contribute to new knowledge on basic inter-city mobility laws, and they have significant applications for regional policies on human mobility.

Disciplinary structure and development strategy of human geography in China - Jie Fan; Pengjun Zhao; Shangyi Zhou; Xiangzheng Deng; Chen Wang (Journal of Geographical Sciences, 2022)

New Target of Oxidative Stress Regulation in Cochleae: Alternative Splicing of the p62/Sqstm1 Gene - Pengjun Li; Dan Bing; Xiaodi Wang; Jin Chen; Zhihui Du; Yanbo Sun; Fan Qi; Hanqi Chu (Journal of Molecular Neuroscience, 2022)

The Relationship of Morphological-Hemodynamic Characteristics, Inflammation, and Remodeling of Aneurysm Wall in Unruptured Intracranial Aneurysms - Qingyuan Liu; Yisen Zhang; Junhua Yang; Yi Yang; Maogui Li; Shanwen Chen; Pengjun Jiang; Nuochuan Wang; Yanan Zhang; Jia Liu; Jun Wu; Shuo Wang (Translational Stroke Research, 2022)

Sequencing and phylogenetic characterization of a novel Polerovirus from Nicotiana tabacum - Yingjie Liu; Yonghao Dong; Xi Chen; Yun Zang; Jinyan Liu; Guangwei Ren; Pengjun Xu (Virus Genes, 2020)

Preference of the aphid Myzus persicae (Hemiptera: Aphididae) for tobacco plants at specific stages of potato virus Y infection - Jinyan Liu; Yingjie Liu; Philip Donkersley; Yonghao Dong; Xi Chen; Yun Zang; Pengjun Xu; Guangwei Ren (Archives of Virology, 2019)

The genome sequence of a novel RNA virus in Adelphocoris suturalis - Xinlian Li; Pengjun Xu; Xianming Yang; He Yuan; Lizhen Chen; Yanhui Lu (Archives of Virology, 2017)

NZ suppresses TLR4/NF-κB signalings and NLRP3 inflammasome activation in LPS-induced RAW264.7 macrophages - Pengjun Xiang; Tong Chen; Yi Mou; Hui Wu; Peng Xie; Guo Lu; Xiaojian Gong; Qinghua Hu; Yihua Zhang; Hui Ji (Inflammation Research, 2015)